A Critical Study of Attitudes of MBBS and BDS Students Towards Their Future Profession - Laxmi Pathak; Aishwarya Verma; Rajeshwar Reddy Kasarla; Chetkant Bhusal; Ritesh Sharma (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION The attitudes of the students play a very vital role in choosing a particular career. The amount of study in MBBS and BDS is signiﬁcantly higher than many other professions. Hence the present study was designed to assess and explore the attitudes of MBBS and BDS students towards their future medical profession. MATERIAL AND METHODS A descriptive, cross-sectional study was conducted by administering online Google Form questionnaire to all MBBS and BDS students (1st year to 4th year) Universal College of Medical Sciences, and College of Dental Surgery, Bhairahawa, Nepal, during the period of 1 October, 2020 to 30 December, 2020, using non-probability purposive sampling. The sample size of the present study is 283 (198 MBBS and 85 BDS). The questionnaire was consisting of 32 statements, both positive as well as negative (Likert scale), on 5 options via strongly disagree, disagree, neutral, agree and strongly agree, was mailed to all students. The students were asked to read each statement carefully and click on their opinion/response. RESULTS The overall mean and standard deviation for MBBS students’ attitude towards their medical profession was 3.73 and 0.87 respec- tively. Similarly, the overall mean and standard deviation for attitude of BDS students’ towards their future profession was 1.60 and 0.37 respectively. CONCLUSION Both MBBS and BDS students were having a positive and right attitude towards their future medical profession.